Approaches to understanding COVID-19 and its neurological associations - Beghi, Ettore; Michael, Benedict D; Solomon, Tom; Westenberg, Erica; Winkler, Andrea S (John Wiley & Sons, Inc., 2021)
There is an accumulating volume of research into neurological manifestations of COVID-19. However, inconsistent study designs, inadequate controls, poorly-validated tests, and differing settings, interventions, and cultural norms weaken study quality, comparability, and thus the understanding of the spectrum, burden and pathophysiology of these complications. Therefore, a global COVID-19 Neuro Research Coalition, together with the WHO, has reviewed reports of COVID-19 neurological complications and harmonised clinical measures for future research. This will facilitate well-designed studies using precise, consistent case definitions of SARS-CoV2 infection and neurological complications, with standardised forms for pooled data analyses that non-specialists can use, including in low-income settings.